Combining citizen science and molecular diagnostic methods to investigate the prevalence of Borrelia burgdorferi s.l. and Borrelia miyamotoi in tick pools across Great Britain - Shan, Jinyu; Jia, Ying; Hickenbotham, Peter; Teulières, Louis; Clokie, Martha R. J. (Frontiers in Microbiology, 2023)
Lyme disease is the most common tick born disease. It is caused by a group of bacteria known as Borrelia burgdorferi sensu lato (s.l.) complex. Borrelia miyamotoi infection is an emerging tick-borne disease. To investigate the prevalence of B. burgdorferi and B. miyamotoi in ticks, first, we developed a PCR (Bmer-qPCR) that targets the phage terminase large subunit (terL) gene carried by B. miyamotoi. A similar approach had been used successfully in developing Ter-qPCR for detecting B. burgdorferi. The terL protein functions as an enzyme in packaging phage DNA. Analytical validation of the Bmer-qPCR confirmed its specificity, efficiency, and sensitivity. Second, we designed a citizen science-based approach to detect thousands of ticks collected from numerous sites across Great Britain. Finally, we applied Bmer-qPCR and Ter-qPCR to 153 tick pools and revealed that the prevalence of B. burgdorferi and B. miyamotoi was dependent on their geographical locations, i.e., Scotland showed higher rate of B. burgdorferi and lower rate of B. miyamotoi carriage as compared to those of England data. A pattern of diminishing rate of B. miyamotoi carriage from southern England to northern Scotland was visible. Together, the citizen science-based approach provided an estimation of the carriage rate of B. burgdorferi and B. miyamotoi in ticks and a potential spreading pattern of B. miyamotoi from the south to the north of Great Britain. Our findings underscore the power of combining citizen science with molecular diagnostic method to reveal hidden pattern of pathogen-host-environment interplay. Our approach can offer a powerful tool to elucidate the ecology of tick-borne disease and may offer guidance for pathogen-control initiatives. In a resource-limited era, monitoring pathogens requires both field and laboratory support, citizen science approach provides a method to empower the public for sample collection. Citizen science approach coupled with laboratory diagnostic test will make real-time monitoring of pathogen distribution and prevalence possible.